1991
DOI: 10.1016/0022-1031(91)90030-a
|View full text |Cite
|
Sign up to set email alerts
|

Requesting information to form an impression: The influence of valence and confirmatory status

Abstract: The present study examines the impact of the valence and the confirmatory status of trait information on impression formation by giving subjects an opportunity to play an active role in their reception of information. In two experiments subjects indicated who, out of a series of candidates, corresponded to an a priori personality profile. These profiles were either positive or negative in tone. Also. whereas some profiles comprised univalent evidence (all personality traits were either positive or negative), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
1
2

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 39 publications
8
56
1
2
Order By: Relevance
“…The presence of an inhibitor and its asymmetric nature provide salient, diagnostic, and readily accessible cues that factor into the anchoring of other perceptions (Dick et al, 1990;Wilson and Brekke, 1994). Such an effect is similar to impression formation (Asch, 1946;Everard and Galletta, 2004;Yzerbyt and Leyens, 1991). Specific to IS, Everard and Galletta supported the theory of negative impression formation toward a Web site, whereby a perception of a flaw led to diminished perceptions of Web site quality.…”
Section: Proposition 3: Inhibitors Are More Explanatory Of Adoption Asupporting
confidence: 52%
See 2 more Smart Citations
“…The presence of an inhibitor and its asymmetric nature provide salient, diagnostic, and readily accessible cues that factor into the anchoring of other perceptions (Dick et al, 1990;Wilson and Brekke, 1994). Such an effect is similar to impression formation (Asch, 1946;Everard and Galletta, 2004;Yzerbyt and Leyens, 1991). Specific to IS, Everard and Galletta supported the theory of negative impression formation toward a Web site, whereby a perception of a flaw led to diminished perceptions of Web site quality.…”
Section: Proposition 3: Inhibitors Are More Explanatory Of Adoption Asupporting
confidence: 52%
“…However, as noted earlier, negative information is more salient (Baumeister et al, 2001), more diagnostic (Skowronski and Carlston, 1987), and tends to instigate greater information processing (Yzerbyt and Leyens, 1991). Even if an enabler takes on a negative valence, the issue becomes one of psychological awareness and the concept that the absence of a positive feature is not as salient as the presence of a negative one (Leyens et al, 1997;Peeters and Czapinski, 1990;Treisman and Gelade, 1980).…”
Section: Proposition 3: Inhibitors Are More Explanatory Of Adoption Amentioning
confidence: 95%
See 1 more Smart Citation
“…The original need-to-evaluate scale contains sixteen items, six of which are reverse-coded in attempts to avoid acquiescence bias, the tendency for individuals to agree with statements regardless of their meaning (Watson & Johnson-Laird, 1972;Yzerbyt and Leyens, 1991). Although inclusion of many items permits the use of reverse-scored items, the full NE scale would be prohibitively expensive to administer in general public surveys.…”
Section: Measure Of Need To Evaluatementioning
confidence: 99%
“…In further support, Afifi and Burgoon's (2000) research on social interaction demonstrates that in the context of a relationship, the reactions to changes in others' behaviors is more pronounced when the shift is from positive to negative versus negative to positive. Similarly, Yzerbyt and Leyens (1991) demonstrated that negative information leads to quick exclusionary judgments, while Skowronski and Carlston (1992) found that the impact of morally positive behavior on one's impressions was easily overridden by new information demonstrating immoral behaviors. Finally, Martijin, Spears, van der Pligt, and Jakobs (1992) found that the severity of negative behaviors affected global assessments of an individual's values more than positive behaviors did.…”
Section: Individual Labeling Processmentioning
confidence: 99%